Relationship between GDP per capita and traffic accidents in Brazilian municipalities, 2005, 2010 and 2015 - Pinheiro, Pedro Cisalpino (2020)
Objective: The main objective of this paper is to analyze the relationship between GDP and three variables related to traffic accidents in Brazilian municipalities: traffic accident mortality, deaths per vehicle; and vehicles per inhabitant. Methods: 2005, 2010 and 2015 terrestrial traffic accident (ATT) mortality rates were estimated using a three years moving average and were standardized, then, we applied the empirical Bayes estimator (EBE). Fatality rates (deaths per vehicle) also were based on EBE. Vehicles per inhabitant considered the ratio between vehicle fleet and the population at municipal level. For every studied year, we estimated linear regression models between GDP and the interest variables.  Results: Variables distribution indicates that, between 2005 and 2015, GDP and vehicles per inhabitant kept the same rising relationship. Fatality rates show a decreasing association with GDP. TA mortality distribution with GDP presented a pattern close to an inverted-U. Model coefficients practically did not change for the vehicle per inhabitant. Estimated association between deaths per vehicle and GDP kept the same sign, but diminished between 2005 and 2015. Model coefficient sign changed in 2015 for TA mortality. Conclusion: Similarly to what was observed in developed countries, the relationship between mortality from traffic accidents and GDP changed in the analyzed period.